An assessment of prevalence and expenditure associated with discharge brain MRI in preterm infants - (:unkn) unknown (My University, 2021)
To assess national expenditure associated with preterm-infant brain MRI and potential impact of reduction per Choosing Wisely campaign 2015 recommendation to “avoid routine screening term-equivalent or discharge brain MRIs in preterm-infants”. Cross-sectional U.S. trend data from the Agency for Healthcare Research and Quality (AHRQ), Healthcare Cost and Utilization Project (HCUP) Kids’ Inpatient Database (KID) database (2006, 2009, 2012, 2016) was used to estimate overall national expenditure associated with brain MRI among infants with gestational age (GA) ≤36 weeks, and also when classified as ‘not indicated’ (NI-MRI) i.e., equivalent to routine use without clinical indications and regarded as low-value service (LVS). Associated cost was determined by querying CMS-database for physician-fee-schedules to find the highest global procedure-cost per cycle, then adjusting for inflation. Sensitivity-analyses were conducted to account for additional clinical charges associated with NI-MRI. 3,768 (0.26%) of 1,472,236 preterm-infants had brain MRI across all cycles (inflation-adjusted total $3,690,088). Overall proportion of brain MRIs increased across 2006–2012 from 0.25%-0.33% but decreased in 2016 to 0.16% (PP for interaction $1.2 million.